Self calibration in a fiber optic sensing system using the entangled photon states walk-off compensation - S. Suchat (2018)
We present a concept of a self calibration of the classical and quantum parameters measurement using a fiber optic system. The measurement of the change in phase of the optimum entangled states visibility, which is performed in term of a walk-off length, i.e. birefringence. The applied two physical parameters (i.e. force/stress and temperature) on the sensing fiber can be simultaneously measured, whereas the self calibration respecting to the entangled photon walk-off length can be performed. The scheme of the entangled photons generation in fiber optic is reviewed and the walk-off on the polarization entangled states presented. The potential of self calibration and simultaneous measurement using an interferometric sensing technique and fiber grating sensor are proposed and discussed. The entangled photon walk-off compensation when the sensing fiber was in the thermal controlled environment presented and discussed. © 2009 Elsevier Ltd. All rights reserved.